The Kager Triangle: An Anatomic Review and Potential Implications for Lymphatic Surgery - Yuma Fuse, MD; James E. Fanning, BS; Travis Boyd, MD; Meera Singhal, BS; Jordan Bohnen, MD; Fernando Raduan, MD; Dhruv Singhal, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Vascularized lymph node transplant (VLNT) is widely performed for chronic upper and lower extremity lymphedema. However, ideal recipient sites for the transplant are still under debate. The placement of VLNTs distally in an extremity can be challenging as the small cross-sectional area of the limb at this level does not allow for flap inset without gross contour deformity, which can adversely impact aesthetic outcomes and preclude fitting of an adequate compression garment. In this article, we introduce the Kager triangle as a potential distal lower extremity VLNT recipient site for the lower extremity. The Kager triangle is bordered by the Achilles tendon, the flexor hallucis longus, and the calcaneus, which accommodates the Kager fat pad, the largest adipose structure in the lower extremity. We transferred an omentum lymph node flap to the Kager triangle, and the posterior tibial artery and the anterior lateral malleolar artery were utilized as recipient vessels in a flow-through fashion. The incisions were directly closed with excellent cosmesis.